Biased random-key genetic algorithms for combinatorial optimization - Gonçalves, José Fernando; Resende, Mauricio G. C. (Journal of heuristics, 2011)
Random-key genetic algorithms were introduced by Bean (ORSA J. Comput. 6:154–160, 1994 ) for solving sequencing problems in combinatorial optimization. Since then, they have been extended to handle a wide class of combinatorial optimization problems. This paper presents a tutorial on the implementation and use of biased random-key genetic algorithms for solving combinatorial optimization problems. Biased random-key genetic algorithms are a variant of random-key genetic algorithms, where one of the parents used for mating is biased to be of higher fitness than the other parent. After introducing the basics of biased random-key genetic algorithms, the paper discusses in some detail implementation issues, illustrating the ease in which sequential and parallel heuristics based on biased random-key genetic algorithms can be developed. A survey of applications that have recently appeared in the literature is also given.